Attachment Avoidance Is Significantly Related to Attentional Preference for Infant Faces: Evidence from Eye Movement Data - Jia, Yuncheng; Cheng, Gang; Zhang, Dajun; Ta, Na; Xia, Mu; Ding, Fangyuan (Frontiers in Psychology, 2017)
Objective: To determine the influence of adult attachment orientations on infant preference. Methods: We adopted eye-tracking technology to monitor childless college women’s eye movements when looking at pairs of faces, including one adult face (man or woman) and one infant face, with three different expressions (happy, sadness, and neutral). The participants (N = 150; 84% Han ethnicity) were aged 18–29 years (M = 19.22, SD = 1.72). A random intercepts multilevel linear regression analysis was used to assess the unique contribution of attachment avoidance, determined using the Experiences in Close Relationships scale, to preference for infant faces. Results: Women with higher attachment avoidance showed less infant preference, as shown by less sustained overt attentional bias to the infant face than the adult face based on fixation time and count. Conclusions: Adult attachment might be related to infant preference according to eye movement indices. Women with higher attachment avoidance may lack attentional preference for infant faces. The findings may aid the treatment and remediation of the interactions between children and mothers with insecure attachment.